FORMULASI DAN UJI AKTIVITAS SABUN CAIR ANTISEPTIK DARI EKSTRAK KULIT BUAH KAPUL (Baccaurea macrocarpa) - Nur Mahdi; Farhandika Putra; Nuraini Manurung (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Kapul fruit is a typical plant of Kalimantan known by the Latin name Baccaurea macrocarpa. The rind of Baccaurea macrocarpa has antibacterial potential, so it is necessary to develop it into liquid soap preparations. The purpose of this study was to formulate and test the antiseptic activity of liquid soap from the extract of Baccaurea macrocarpa rind. Kapul fruit peel extract was divided into 4 different concentrations (F0 0%, FI 1%, FII 2%, and FIII 3%) formulated in liquid soap preparations. The evaluation of liquid soap includes physical characteristics (organoleptic, homogeneity, dispersion test), pH, and antibacterial test. The results of the organoleptic test, dispersive test, pH, antibacterial test Kapul fruit rind extract showed no significant difference in the pH, dispersibility, and antibacterial test. Based on the results of the evaluation of the preparations, all formulas showed good characteristics. The formula I has a good antibacterial effect.